HPD-Kit: a comprehensive toolkit for pathogen detection and analysis - Que, Tengcheng; Li, Wen; Zhang, Zhining; He, Yunlin; He, Kangming; Qiu, Hong; Huang, Juan; Lu, Zhiwei; Jiang, Chunlan; Huang, Yongjian; Huang, Hui; Wu, Qiuyu; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionUnbiased metagenomic sequencing (mNGS) is crucial for infectious disease diagnosis and epidemiological surveillance. However, its analysis requires specialized bioinformatics skills, creating barriers for clinicians. We developed HPD-Kit (Henbio Pathogen Detection Toolkit) with an integrated pathogen database to simplify pathogen detection and analysis for both human and animal pathogens.MethodsHPD-Kit includes a specifically curated pathogen database and optimized bioinformatics pipeline. We evaluated its performance using simulated datasets at varying pathogen abundances and clinical samples. The toolkit provides both open-source software and a web interface for streamlined one-click analysis.ResultsValidation with simulated data showed HPD-Kit maintains high detection accuracy even at low pathogen abundance. Clinical dataset analysis demonstrated superior pathogen identification compared to conventional methods. The web interface retained this performance while significantly improving usability.DiscussionHPD-Kit effectively addresses the bioinformatics barrier in mNGS analysis while maintaining high accuracy. Its dual open-source and web-based implementation facilitates clinical and public health applications, promoting wider adoption of mNGS technology in diagnostic settings.